2004
DOI: 10.1243/146808704323224231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pilot injection timing, pilot quantity and intake charge conditions on performance and emissions for an advanced low-pilot-ignited natural gas engine

Abstract: Diesel engines may be converted readily to operate Introduction primarily on natural gas using the injection of a diesel pilotDiesel engines are widely used for heavy-duty applito achieve ignition. Advanced low-pilot-ignited natural gas cations and especially for the propulsion of trucks. (ALPING) engines show significant potential to matchEven though the efficiency of these engines is very diesel engines in their part-load and full-load efficiencies.high there are some major problems associated with Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 4 publications
3
18
0
1
Order By: Relevance
“…Numerous research works on experimental and theoretical investigations concerning the dual fuel diesel-natural gas operating mode have been reported over the last decades in the literature [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research works on experimental and theoretical investigations concerning the dual fuel diesel-natural gas operating mode have been reported over the last decades in the literature [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Moreover, the effects of some important parameters, such as pilot diesel fuel quantity, pilot injection timing, natural gas percentage, natural gas composition, and intake air temperature have also been studied. [12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%
“…Being a low carbon fuel, natural gas produces lower carbon dioxide emissions and generates lower particulate matter (PM) emissions than diesel fuel when burned in an internal combustion engine [1][2][3]. Since heavy duty engine industry predominately uses diesel fuel, replacing diesel fuel by natural gas in internal combustion engines will reduce emissions of carbon dioxide and particulate matter from heavy duty engine industry.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 Copyright © 2015 by ASME diesel injection timing in [6,7] was fixed. During the studies of pilot-ignited dual fuel combustion, Alla et al [8], Singh et al [2], Krishnan et al [9] and Srinivasan et al [10] found that a change in diesel injection timing had a significant effect on the combustion performance of dual fuel combustion. The combustion performance of dual fuel combustion could also be affected by intake conditions [2,9], exhaust gas recirculation [11], and cetane number of diesel fuel [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation